Modeling PNPLA3‐Associated NAFLD Using Human‐Induced Pluripotent Stem Cells. Issue 6 (27th September 2021) - Tilson, Samantha G.; Morell, Carola M.; Lenaerts, An‐Sofie; Park, Seung Bum; Hu, Zongyi; Jenkins, Benjamin; Koulman, Albert; Liang, T. Jake; Vallier, Ludovic
Abstract : Background and Aims: NAFLD is a growing public health burden. However, the pathogenesis of NAFLD has not yet been fully elucidated, and the importance of genetic factors has only recently been appreciated. Genomic studies have revealed a strong association between NAFLD progression and the I148M variant in patatin‐like phospholipase domain‐containing protein 3 (PNPLA3). Nonetheless, very little is known about the mechanisms by which this gene and its variants can influence disease development. To investigate these mechanisms, we have developed an in vitro model that takes advantage of the unique properties of human‐induced pluripotent stem cells (hiPSCs) and the CRISPR/CAS9 gene editing technology. Approach and Results: We used isogenic hiPSC lines with either a knockout (PNPLA3 KO ) of the PNPLA3 gene or with the I148M variant (PNPLA3 I148M ) to model PNPLA3‐associated NAFLD. The resulting hiPSCs were differentiated into hepatocytes, treated with either unsaturated or saturated free fatty acids to induce NAFLD‐like phenotypes, and characterized by various functional, transcriptomic, and lipidomic assays. PNPLA3 KO hepatocytes showed higher lipid accumulation as well as an altered pattern of response to lipid‐induced stress. Interestingly, loss of PNPLA3 also caused a reduction in xenobiotic metabolism and predisposed PNPLA3 KO cells to be more susceptible to ethanol‐induced and methotrexate‐induced toxicity. The PNPLA3 I148M cells exhibited an intermediate phenotype between the wild‐type and PNPLA3 KO cells. Conclusions: Together, these results indicate that the I148M variant induces a loss of function predisposing to steatosis and increased susceptibility to hepatotoxins.